Gulf Cooperation Council : Trade and Foreign Investment-Keys to Diversification and Growth in the GCC. (Policy Papers; Policy Paper ;, 2018)
Diversification of the GCC economies, supported by greater openness to trade and higher foreign investment, can have a large impact on growth. Such measures can support higher, sustained, and more inclusive growth by improving the allocation of resources across sectors and producers, creating jobs, triggering technology spillovers, promoting knowledge, creating a more competitive business environment, and enhancing productivity. The GCC countries are open to trade, but much less so to foreign direct investment (FDI). GCC foreign trade has been expanding robustly, but FDI inflows have stalled in recent years despite policy efforts taken to reduce administrative barriers and provide incentives to attract FDI. Tariffs are relatively low; however, a number of non-tariff barriers to trade persist and there are substantial restrictions on foreign ownership of businesses and real estate. The growth impact of closing export and FDI gaps could be significant. In most countries, the biggest boost to growth would come from closing the FDI gap-up to one percentage point increase in real non-oil per capita GDP growth. Closing export gaps could provide an additional growth dividend in the range of 0.2-0.5 percentage point. Boosting non-oil exports and attracting more FDI requires a supportive policy environment. Policy priorities are to upgrade human capital, increase productivity and competitiveness, improve the business climate, and reduce remaining barriers to foreign trade and investment. Specifically, continued reforms in the following areas will be important: -- Human capital development: continue with investments made to raise educational quality to provide knowledge and skills upgrade. -- Labor market reforms: aim to improve productivity and boost competitiveness of the non-oil economy. -- Legal frameworks: ensure predictability and protection; efforts should include enhancing minority investor protection and dispute resolution; implementing anti-bribery and integrity measures. -- Business climate reforms: focus on further liberalizing foreign ownership regulations and strengthening corporate governance; and on further reducing non-tariff trade barriers by streamlining and automating border procedures and streamlining administrative processes for issuing permits.